A Protocol for Identifying and Sampling From Proxy Populations. - Lu, Tao; Franklin, Aimee L. (Social Science Quarterly (Wiley-Blackwell), 2018)
Objectives: Increasingly it is more and more difficult for researchers to garner a robust response rate from their target population. In response, they often turn to more accessible proxy populations. However, guidance on how to identify and select a proxy population that reasonably mimics the target population is neither expansive nor systematic. Our objective is to fill this gap by offering a standardized protocol for selecting appropriate population. We introduce a proxy selection protocol that combines convenience with purposive nonprobability sampling. Methods: The protocol introduces a method following a step‐by‐step process to evaluate the suitability of a different potential proxy populations as a reasonable representation of the target population. Results and Conclusion: We come to an conclusion that this proxy selection protocol can overcome low response rates and avoid contamination of a limited target population when conducting exploratory or early‐stage explanatory research of potential causal relationships.